Studying evaporating black hole using quantum computation algorithms on IBM quantum processor - Ritu Dhaulakhandi; Raikhik Das; Bikash K. Behera; Felix J. Seo (AIP Advances)
Analyzing complex quantum systems using quantum computational algorithms is one of the most promising applications of quantum computers. This study focuses on evaluating the performance of a custom variational ansatz in the Variational Quantum Eigensolver (VQE) algorithm compared to predefined ansatzes. To achieve this, we employ the evaporating black hole model as a test bed for our analysis. Using the VQE approach, which integrates quantum and classical computing techniques, we aim to minimize the energy expectation value of the Hamiltonian. By training the circuit parameters of a trial wave function as a parameterized quantum circuit, we determine the upper bound for the ground state energy and assess the optimal variational form. We define a custom ansatz for the VQE protocol and compare its performance with other predefined ansatzes. Additionally, we test the performance of three different classical optimizers to further understand their impact on the VQE algorithm’s efficiency and accuracy.